Diagnozowanie skręcenia stawu skokowego = Diagnosis of ankle sprain - Kaźmierczak, Urszula; Kwiatkowski, Szymon; Radzimińska, Agnieszka; Strojek, Katarzyna; Weber-Rajek, Magdalena; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Kaźmierczak Urszula, Kwiatkowski Szymon, Radzimińska Agnieszka, Strojek Katarzyna, Weber-Rajek Magdalena, Zukow Walery. Diagnozowanie skręcenia stawu skokowego = Diagnosis of ankle sprain. Journal of Education, Health and Sport. 2016;6(12):441-451. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.206008 http://ojs.ukw.edu.pl/index.php/johs/article/view/4075 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 16.12.2016. Diagnozowanie skręcenia stawu skokowego Diagnosis of ankle sprain Urszula Kaźmierczak1, Szymon Kwiatkowski1, Agnieszka Radzimińska¹, Katarzyna Strojek¹, Magdalena Weber-Rajek¹, Walery Zukow² 1Department of Physiotherapy, Division of Principles of Physiotherapy, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Bydgoszcz, Poland 2Kazimierz Wielki University, Bydgoszcz Słowa kluczowe: staw skokowy, diagnozowanie, skręcenie, skręcenie stawu skokowego Keywords: ankle, diagnosis, sprain, ankle sprain Streszczenie Postawienie prawidłowej diagnozy po skręceniu stawu skokowego jest kluczowym elementem pozwalającym zaplanować i wdrożyć odpowiednie leczenie. Należy w tym celu przeprowadzić dokładne badanie podmiotowe, czyli szczegółowy wywiad z pacjentem, a następnie badanie przedmiotowe. Jego elementami są obserwacja i palpacja, testy funkcjonalne oraz badania dodatkowe. Działanie takie pozwala nabrać pewności na temat tego, które struktury i w jakim stopniu zostały uszkodzone.Uraz skrętny stawu skokowego może wiązać się nie tylko z uszkodzeniem więzadeł czy torebki stawowej, ale również powstawanie ukrytych problemów. W przypadku przeoczenia, mogą znacznie przedłużyć proces powrotu do zdrowia. Abstract Making the right diagnosis after spraining an ankle is a key element that allows to plan and implement appropriate treatment. A medical history which is a detailed interview with a patient and then physical examination should be undertaken. The components of the latter are observation and palpation, functional tests and additional examinations. Such a proceeding enables ensuring which structures and to which extend got damaged. The torsion injury of the ankle may be associated with not only the damage of the joint capsule or ligaments, but also the formation of hidden problems. Those, when overlooked, may substantially extend the process of recovery.